The upper Palaeozoic Godar-e-Siah Complex of Jandaq: Evidence and significance of a North Palaeotethyan succession in Central Iran. (1st May 2017) - Berra, Fabrizio; Zanchi, Andrea; Angiolini, Lucia; Vachard, Daniel; Vezzoli, Giovanni; Zanchetta, Stefano; Bergomi, Maria; Javadi, Hamid Reza; Kouhpeyma, Meyssam
Graphical abstract: Highlights: The Godar-e-Siah Complex of Central Iran is a fragment of the Palaeotethys suture. The active margin related magmatic arc is Carboniferous based on U-Pb zircon ages. The Godar-e-Siah faunas show a N-Palaeotethyan affinity. Abstract: The Upper Palaeozoic Godar-e-Siah Complex of Jandaq, Central Iran, comprises three isolated, fault-bounded outcrops exposing Palaeozoic fossiliferous carbonates, volcanics and siliciclastics, which are markedly distinct from the surrounding sedimentary successions. The three outcrops, that emerge below Cretaceous and younger sediments, are the Chah Rizab outcrop, the Godar-e-Siah northern outcrop, and the Godar-e-Siah central outcrop. Their sedimentary successions strongly differ from the typical passive margin successions of Gondwanan affinity that characterize the Yazd, Lut and Tabas blocks of Central Iran and the Alborz in North Iran. To understand the origin of these profound differences, we first calibrated the age of the Jandaq successions: U-Pb radiometric zircons ages, obtained from granitoid boulders in the conglomerates at Chah Rizab and in the Godar-e-Siah northern outcrop, gave a Late Devonian to Mississippian age. Biostratigraphic data from brachiopods and fusulinids from the Godar-e-Siah northern and central outcrops indicate a Pennsylvanian age. The age of the successions is thus post-Visean to Pennsylvanian. The petrographic composition of the siliciclastic deposits indicates the erosion of a magmatic arc. To understand where the Jandaq complex could have been located at that time, we have assessed the palaeobiogeographic affinity of the faunas. The collected brachiopods and fusulinids assemblages are mostly similar to coeval faunas from Spain, Donbass, Urals, and Yukon Territory (Canada) and have a North-Palaeotethyan affinity. The Godar-e-Siah Complex of Jandaq likely represents part of the southern active margin of Eurasia (northern margin of the Palaeotethys), in contrast to the surrounding Central and North Iran blocks, which were at that time located along the southern margin of the Neotethys. Our investigations confirm a complex palaeogeographic evolution for the studied outcrops, suggesting that they represent fragments of the southern Eurasian active margin - today preserved in NE Iran - displaced by crustal-scale wrench motions related to the opening and closure of the Sabzear Ocean and to the Cenozoic activity of the Great Kavir-Doruneh Fault and its possible precursors.